Daya Antelmintik Serbuk Kulit Nanas (Ananas comosus) terhadap Cacing Haemochus contortus pada Domba - Dewi Pranatasari; Rido Florensius Manik; Budi Purwo Widiarso; Wida Wahidah Mubarokah (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2021)
The problem facing sheep breeders in breeding sheep was digestive tract parasite of worm (nematodiasis and haemonchosis). Resistance to anthelmintics was the reason for the study of alternative medication of H. contortus infection. It aimed at finding out the effectiveness of the application of pineapple peel powder as H. contortus anthelmintic in sheep and the dose of the pineapple peel powder as the H. contortus anthelmintic. It used 15 sheep that were assigned to 5 groups. Group I served as positive control with the application of albendazole (Kalbazen) anthelmintic, Group II was treated using the pineapple peel powder at the dose of 150 mg/kg BW. Group III was treated using the pineapple peel powder at the dose of 200 mg/kg BW. Group IV was treated using the pineapple peel powder at the dose of 250 mg/kg BW. And, Group V served as negative control without any treatment. The treatments were conducted for 14 days and the resulting statistic data were analyzed using comparative descriptive method by comparing initial data (before the treatments) and final data (after the treatments). The comparative data showed that there was significant change in the observed variables. The results of the study showed that the pineapple peel powder could be used as the anthelmintic of the H. contortus in the sheep and the dose of 250 mg/kg BW most significantly decreased the mean number of the eggs of the worm per gram of feces